Level of mastery of spiking technique among male university students in physical education classes incorporating volleyball elements - Dvornikov A.V.; Voloshin N.A. (Theory and Practice of Physical Culture, 2024)
This article presents the results of assessing the level of mastery of the spiking technique by students learning the fundamentals of volleyball in university physical education classes.